The Massacres Commemorated in Iraqi Turkmen Culture and Political Discourse - (:unkn) unknown (My University, 2021)
After the collapse of the Ottoman Empire, Iraqi Turkmen lost their influence over the authority of Iraq. Foryears, the Iraq government formed its policy based on ignoring and eliminating the Iraqi Turkmen because thefirst of king of Iraq who was King Faysal I, saw the Turks as a threat to his state and policy. Therefore, theIraqi Turkmens faced many times massacres by the Iraqi state. Each massacre has deeply influenced IraqiTurkmen, especially, influenced their literature, history and memories of their life. Hence, as a theoreticalconcept collective memory helps us to understand how Iraqi Turkmen images of the massacres and its influencein their memory. In this study will be analysed the impact of these massacres between 1924 and 1991, on IraqiTurkmen on their history, literature, poem, stories and so on. In this study, the prominent works of IraqiTurkmen such as poems and stories and the books written in this field will be discussed with the method ofdocument analysis.

Osmanlı İmparatorluğu'nun yıkılmasından sonra Irak Türkmenleri Irak’taki otoritelerini kaybetti. Irak hükümetleri yıllarca Irak Türkmenlerini göz ardı etti ve bu doğrultuda politikalarını oluşturdu. Irak Kralı I. Faysal Irak Türkmenlerini, Irak devletine ve politikasına karşı tehdit olarak gördü. Bu nedenle Irak Türkmenleri Irak devleti tarafından defalarca katliamlara maruz kaldı. Her katliam Irak Türkmenlerini derinden etkiledi, özellikle de edebiyatlarını, tarihlerini ve hatıralarını. Bu nedenle, teorik bir kavram olarak kolektif bellek, Iraklı Türkmenlerin uğradığı katliamların etkilerini ve hafızalarındaki yeri anlamamıza yardımcı olmaktadır. Bu çalışmada Irak Türkmenlerine 1924-1991 yılları arası yapılan katliamların Irak Türkmenleri üzerindeki tarihi, edebiyatı, şiiri, öyküleri vb. üzerindeki etkilerinin incelenmesi amaçlanmıştır. Bu çalışmada öne çıkan Irak Türkmenlerinin şiir, hikâye gibi eserleri ve bu alanda yazılan kitaplar döküman analizi yöntemiyle ele alınacaktır
Irak Türkmen Kültüründe ve Siyasi Söylemlerinde Katliamlarin Anılması